Determination of Gliadin as a Measure of Gluten in Food by R5 Sandwich ELISA RIDASCREEN® Gliadin Matrix Extension: Collaborative Study 2012.01. (16th November 2021) - Lacorn, Markus; Dubois, Tina; Weiss, Thomas; Zimmermann, Lisa; Schinabeck, Teresa-Maria; Loos-Theisen, Simone; Scherf, Katharina
Abstract: Background: According to Codex Alimentarius, food products containing less than 20 mg/kg gluten can be labeled as "gluten-free." Since 2002, the R5 antibody method allowed determination of gluten levels and led to a huge improvement of products available to celiac disease (CD) patients. Method: The R5-containing test kit RIDASCREEN ® Gliadin in combination with the cocktail solution was endorsed as Codex Type 1 Method in 2006 based on a collaborative study with corn-based bread, rice-based dough, wheat starches, rice, and corn flour. In 2012, the method was approved as First Action Official Method SM 2012.01 with an "in foods" claim. For Final Action in 2016, the matrix claim was reduced to rice- and corn-based matrixes. Objective: Therefore, R-Biopharm decided to start a collaborative study to demonstrate the wide applicability of Official Method 2012.01 for the quantitative analysis of gliadin in soy, starches, pseudo cereals, legumes, spices, juice, nut nougat crème, cream cheese, pesto, meat, vegetarian meat alternative, cookies, dessert, cake, fish, bread, candies, and potatoes. Materials for incurring were the MoniQA wheat flour and the PWG gliadin preparation. Results: Gliadin levels ranged from 3.4 up to 27.4 mg gliadin per kg. The results of the collaborative study with 14 participating laboratories showed recoveries ranging from 80 to 130%. Relative reproducibility standard deviations for contaminated samples were between 9.8 and 27.7%. Conclusions: The collaborative study results confirmed that the method is accurate and suitable to measure gliadin in important gluten-free food matrixes. Highlights: The title and applicability statement of Official Method 2012.01 were changed as proposed.